Dental Resorption in Gorham-Stout Syndrome - T, Chackartchi; G, Tobias; J, Mann; M, Findler (Archives of Clinical and Medical Case Reports, 2022)
Background: Lymphomatosis Gorham-Stout syndrome is a rare disease involving two pathological processes: Infiltration of nonmalignant, aberrant lymphatic vessels into soft and hard tissues and bone lysis. The syndrome is also known as "vanished bone disease", "disappearing bone disease" and "massive osteolysis phenomenon". Its etiology and pathophysiology are unknown. This report will describe a patient suffering from Lymphomatosis – Gorham – Stout Syndrome presenting to the oral medicine department with external dental cervical resorption. The absorption of tooth material was attributed to an aggressive invasion of soft tissue into the dentin, resembling the pathological process responsible for bone disappearance. The rate of cervical external resorption was found to be related to disease progression. Methods: All the radiographic records of the patient were collected and compared, including three full mouth peri-apical series. Conclusion: This is the first report of the relationship between dental resorption and a systemic disease. The rate of resorption correlated with the destructive activity of the disease. Since the clinical course of the disease followed the dental resorption rate, we can assume that both bone lysis and root resorption are part of the same process. Therefore, dental periapical radiographs may be effective in monitoring disease severity.